2018
DOI: 10.1186/s12864-017-4400-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated ovarian mRNA and miRNA transcriptome profiling characterizes the genetic basis of prolificacy traits in sheep (Ovis aries)

Abstract: BackgroundThe highly prolific breeds of domestic sheep (Ovis aries) are globally valuable genetic resources for sheep industry. Genetic, nutritional and other environmental factors affect prolificacy traits in sheep. To improve our knowledge of the sheep prolificacy traits, we conducted mRNA-miRNA integrated profiling of ovarian tissues from two pure breeds with large (Finnsheep) vs. small (Texel) litter sizes and their F1 crosses, half of which were fed a flushing diet.ResultsAmong the samples, 16,402 genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 76 publications
5
37
0
Order By: Relevance
“…A total of 31 ewes representing three breed groups (Finnsheep (n = 11), Texel (n = 11) and F1 crosses (n = 9) were included in the main experiment (please note that only 18 of the 31 ewes have been included in this study) of which approximately half of the ewes from each breed were kept on the flushing diet. Analyses were conducted for two different time points during the establishment of pregnancy: the follicular growth phase [13] and early pregnancy prior to implantation (current study). After ovary removal, the ewes were mated using two Finnsheep rams, and the pregnant ewes were slaughtered during the preimplantation phase of the pregnancy when the embryos were estimated to be one to three weeks old (Table S1).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 31 ewes representing three breed groups (Finnsheep (n = 11), Texel (n = 11) and F1 crosses (n = 9) were included in the main experiment (please note that only 18 of the 31 ewes have been included in this study) of which approximately half of the ewes from each breed were kept on the flushing diet. Analyses were conducted for two different time points during the establishment of pregnancy: the follicular growth phase [13] and early pregnancy prior to implantation (current study). After ovary removal, the ewes were mated using two Finnsheep rams, and the pregnant ewes were slaughtered during the preimplantation phase of the pregnancy when the embryos were estimated to be one to three weeks old (Table S1).…”
Section: Experimental Designmentioning
confidence: 99%
“…The native Finnsheep, one of the most highly prolific breeds, has been exported to more than 40 countries to improve local breeds [9]. In recent years, a FecG F (V371M) mutation in gene GDF9 has been identified to be strongly associated with litter size in Finnsheep and breeds such as the Norwegian White Sheep, Cambridge and Belclare breeds, which were developed using Finnsheep [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the mRNA and miRNA expression patterns in European mouflon and sheep, a research (Yang et al, 2018) found several key mRNAs, such as INHBA, SPP1, and ZP2, and miRNAs, such as miR-374a and miR-9-5p, which may be responsible for the success of female sheep reproduction. Pokharel et al (2018) detected and characterized some key miRNAs and mRNAs in sheep ovary which may be responsible for sheep prolificacy. Thereby, the identification and functional analysis of mRNAs and miRNAs and characterization of their mutual interaction through sequencing technology may provide new insights into the prolific mechanism in STH sheep with the FecB ++ genotype, which has so far been difficult to elucidate using standard approaches.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-Seq) has been proven to be an efficient method for studying the regulation of gene expression (Wang et al, 2009). In recent years, RNA-Seq has been applied to domestic animals, with a major focus on productivity traits (Bai et al, 2016; Li et al, 2016; Pokharel et al, 2018; Silva-Vignato et al, 2017). A number of transcriptome studies have been conducted in different Holstein breeds (Bai et al, 2016; Li et al, 2016; Sandri et al, 2015), but to date, there are no reports on gene expression studies in either Yakutian cattle or Northern Finncattle.…”
Section: Introductionmentioning
confidence: 99%